Fine Structure and Olfactory Reception of the Labial Palps of Spodoptera frugiperda - Chen, Qiuyan; Liu, Xiaolan; Cao, Song; Ma, Baiwei; Guo, Mengbo; Shen, Jie; Wang, Guirong (Frontiers in Physiology, 2021)
The olfactory system of insects is essential in many crucial behaviors, such as host seeking, mate recognition and locating oviposition sites. Lepidopteran moths possess two main olfactory organs including antennae and labial palps. Compared to antennae, the labial palps are relatively specific and worthy of further investigation due to the labial-palp pit organ (LPO), which contains a large number of sensilla located on the tip segment. The fall armyworm, Spodoptera frugiperda is a worldwide lepidopteran pest, which can damage more than 350 plants and cause significant economic losses. In this study, we surveyed the structure of the labial palps and LPO of S. frugiperda using a super-high magnification lens zoom 3D microscope. Then the distribution and fine structure of sensilla located in the LPO of S. frugiperda were investigated using scanning electron microscopy (SEM). Subsequently, the electrophysiological responses of labial palps to CO2 and 29 plant volatiles were recorded by using electrolabialpalpography (ELPG). Our results showed the fine structure of labial palps, the LPO, and the sensilla located in the LPO of S. frugiperda. Moreover, we demonstrated that the labial palps are olfactory organs that respond to both CO2 and other volatile compounds. Our work established a foundation for further study of the roles of labial palps in insect olfactory related behaviors. Further investigations on the function of labial palps and their biological roles together with CO2 and volatile compound responses in S. frugiperda are necessary, as they may provide better insect behavioral regulators for controlling this pest.